Manhaj Tafsir Al-Maraghi Karya Syekh Ahmad Mustafa Al-Maraghi : Analisis Metode Umum dan Metode Khusus Tafsir Pada Q.S At-Tahrim - Muhamad Iqbal Mustofa; Apriani, Laelati Dwina; Zhilal Fajar Firdaus (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Interpretation of the Qur'an cannot be separated from the tendencies and aspects that influence it, namely the interpreter himself. Syekh Musthofa Al-Maraghi's Tafsir Al-Maraghi is a work of modern tafsir which can be said to be one of the best tafsir works of its time. Syekh Al-Maraghi offers a very simple style and color of interpretation and sentence structure patterns that are easy to understand while maintaining consistency and explanation of the problem. factually, systematically within the scope of the discussion theme, it is also supported by the inclusion of supporting histories. Therefore, this research seeks to explain the manhaj or tendencies of the book of interpretation of Al-Maraghi by Sheikh Ahmad Mustafa Al-Maraghi on QS. At-Tahrim which is seen both in terms of sources, specific and general methods. This research uses qualitative methods with descriptive analysis techniques and literature study to collect data. The results of the research are that in the interpretation of QS. At-Tahrim the author found that the source of the interpretation of the Al-Maraghi tafsir book is bi al-ra'yi. The style of interpretation in Al-Maraghi's tafsir is Adabi Al-Ijtima'i in accordance with the aim of the book of tafsir to be an answer to social problems, the general method uses a tahlili approach, while the special method is to explain the munasabah with the previous letter, presenting one or a group of verses, Syarh al-mufrodat (explanation of important words), presenting ma'na al-jumal, detailing the explanation of the verse, explaining the verse with presents history, also presents asbab nuzul.